2020
DOI: 10.1093/cid/ciaa1525
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Digital Health Equity: A Policy Paper of the Infectious Diseases Society of America and the HIV Medicine Association

Abstract: The SARS-CoV-2 virus pandemic has revolutionized the practice of ambulatory medicine, triggering rapid dissemination of digital healthcare modalities, including synchronous video visits. However, social determinants of health, such as age, race, income, and others, predict readiness for telemedicine and individuals who are not able to connect virtually may become lost to care. This is particularly relevant to the practice of Infectious Diseases (ID) and HIV Medicine, as we care for high proportions of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 16 publications
3
93
0
Order By: Relevance
“…Recommendations at the level of health care organizations and health systems have been more varied. These have included encouragement to develop quality improvement activities focused on underserved or marginalized communities [ 12 , 18 , 27 ], educational initiatives for providers and leaders [ 12 , 23 , 29 , 33 ], and the collection of metrics that provide insight into equity-related outcomes [ 12 ]. Specific advice to clinicians has included strategies such as carefully planning a mix of in-person and virtual visits for clients especially at risk of poor health outcomes during the pandemic [ 25 ], and using telephone-based visits (over video visits) when a patient has access to a telephone but not a device that would enable a video visit [ 25 , 26 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations at the level of health care organizations and health systems have been more varied. These have included encouragement to develop quality improvement activities focused on underserved or marginalized communities [ 12 , 18 , 27 ], educational initiatives for providers and leaders [ 12 , 23 , 29 , 33 ], and the collection of metrics that provide insight into equity-related outcomes [ 12 ]. Specific advice to clinicians has included strategies such as carefully planning a mix of in-person and virtual visits for clients especially at risk of poor health outcomes during the pandemic [ 25 ], and using telephone-based visits (over video visits) when a patient has access to a telephone but not a device that would enable a video visit [ 25 , 26 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the level of policy and government, recommendations have focused on strategies for health policy makers and health care funders to enable access both to the infrastructure required for patients to participate in virtual care (ie, inclusive design standards, broadband internet, and digital devices) and the availability of virtual care services to entire populations (eg, by appropriately reimbursing virtual care) [13,15,23,25,[30][31][32][33]. In addition, policy-focused recommendations have emphasized the clarity of public health messaging about COVID-19 and related restrictions, and the role of digital technologies in enhancing the accuracy and reach of such messaging [24,29].…”
Section: Recommended Strategies To Promote Health Equitymentioning
confidence: 99%
“…This is in stark contrast to 71.9%, reported by Langford et al in a recently published meta-analysis and 71% reported by Nori et al during the March to May pandemic surge period in New York [ 10 , 11 ]. This may be accounted by rapid confirmatory diagnosis of SARS-CoV-2 infection as the cause of pneumonia in our setting, and the vast majority of patients having non-severe infections [ 12 ]. To prepare for the pandemic, the AMS team was requested by the hospital management to work with hospital pharmacy to provide recommendations on alternative antimicrobial use in anticipation of possible drug shortfall.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations at the level of health care organizations and health systems have been more varied. These have included encouragement to develop quality improvement activities focused on underserved or marginalized communities [12,18,27], educational initiatives for providers and leaders [12,23,29,33], and the collection of metrics that provide insight into equity-related outcomes [12]. Specific advice to clinicians has included strategies such as carefully planning a mix of in-person and virtual visits for clients especially at risk of poor health outcomes during the pandemic [25], and using telephone-based visits (over video visits) when a patient has access to a telephone but not a device that would enable a video visit [25,26,28,29].…”
Section: Recommended Strategies To Promote Health Equitymentioning
confidence: 99%